Abaloparatide - Irtiqa Ayani Rathore; Sana Bashir; Vishal R Tandon; Sudhaa Sharma; Annil Mahajan (Dr. Annil Mahajan, 2024)
Abaloparatide is a synthetic peptide analog of human parathyroid hormone-related protein (PTHrP). In 2017, the FDA approved its use in postmenopausal women with osteoporosis at high risk for fracture. Abaloparatide demonstrated a beneficial effect on BMD compared to teriparatide for postmenopausal women with osteoporosis and the prevalence of hypercalcemia in the abaloparatide is less than that of teriparatide. Abaloparatide significantly increased BMD at non-vertebral sites and significantly decreased the risk of major osteoporotic fractures compared with teriparatide. Patients who are intolerant or have failed to respond to traditional osteoporosis therapy are often prescribed abaloparatide.